Facies Carbonate Sedimentology and Paleoecology - Tucker, Maurice; Kiessling, Wolfgang; Munnecke, Axel.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The journal is open to papers dealing with the interpretation of ancient and modern biotopes and carbonate depositional environments by means of facies analysis in its broadest sense. Once the central part of research in hydrocarbon exploration, facies analysis more and more integrates modern and ancient biogeological processes of a changing earth. Special emphasis is laid on paleobiology and -ecology, basin evolution, sedimentology including diagenesis and geochemistry, as well as studies emphasising the impact of life on earth history. The main part of the target group will be people in academia.
Keywords: Geochemistry; Sedimentology; Geobiology; Ecology; Sedimentology; Biogeosciences; Geochemistry; Paleontology; Ecology